Alantolactone Improves Prolonged Exposure of Interleukin-6-Induced Skeletal Muscle Inflammation Associated Glucose Intolerance and Insulin Resistance - Kim, Minjee; Song, Kwangho; Kim, Yeong Shik (Frontiers in Pharmacology, 2017)
The pro-inflammatory cytokine, IL-6, has been proposed to be one of the mediators that link chronic inflammation to glucose intolerance and insulin resistance. Many studies have demonstrated the effects of IL-6 on insulin action in the skeletal muscle. However, few studies have investigated the effect of long-term treatment of IL-6, leading to glucose intolerance and insulin resistance. In the present study, we observed protective effects of alantolactone, a sesquiterpene lactone isolated from Inula helenium against glucose intolerance and insulin resistance induced by prolonged exposure of IL-6. Alantolactone has been reported to have anti-inflammatory and anti-cancer effects through IL-6-induced signal transducer and activator of transcription 3 (STAT3) signaling pathway. The relationship between IL-6 exposure and expression of toll-like receptor 4 (TLR4), involved in inflammation in the skeletal muscle, and the underlying mechanisms were investigated. We observed maximum dysregulation of glucose uptake after 40 ng/ml IL-6 induction for 24 h in L6 myotubes. Prolonged IL-6 exposure suppressed glucose uptake regulating alpha serine/threonine-protein kinase (AKT) phosphorylation; however, pretreatment with alantolactone activated AKT phosphorylation and improved glucose uptake. Alantolactone also attenuated IL-6-stimulated STAT3 phosphorylation, followed by an increase in expression of negative regulator suppressor of cytokine signaling 3 (SOCS3). Furthermore, IL-6-induced expression of pathogen recognition receptor, TLR4, was also suppressed by alantolactone pretreatment. Post silencing of STAT3 using siRNA approach, IL-6-stimulated siRNA-STAT3 improved glucose uptake and suppressed TLR4 gene expression. Taken together, we propose that, as a STAT3 inhibitor, alantolactone, improves glucose regulation in the skeletal muscle by inhibiting IL-6-induced STAT3-SOCS3 signaling followed by inhibition of the TLR4 gene expression. Therefore, alantolactone can be a promising candidate for the treatment of inflammation-associated glucose intolerance and insulin resistance.